Strategi Penggunaan Teknologi dalam Meningkatkan Profesionalisme Guru Bahasa Arab di Era 4.0 - Hairus Sodik (Institut Kariman Wirayudha Sumenep, 2023)
Along with increasing competition in this increasingly sophisticated era, the competence of Arabic language teachers has become a necessity that cannot be ignored. Because teachers are responsible for imparting knowledge and developing ideas and enthusiasm to be able to survive in increasingly competitive times, it is very important to improve their abilities professionally. This research method uses library research, by reviewing several literatures related to technology strategies in increasing the professionalism of Arabic language teachers. The results of this research are that a qualified teacher needs to continue to be prepared so that he can keep up with developments in society, especially those related to advances in technology and information. Technological innovations in communication and information must be used by a skilled teacher to improve teaching and develop personal skills. Therefore, a teacher must be able to keep up with the times and continue to increase knowledge through this. Indirectly, technology will influence performance as a professional educator so that it will produce graduates who are ready to enter society with the abilities they have.